Antibacterial and photochemical properties of cellulose nanofiber-titania nanocomposites loaded with two different types of antibiotic medicines - Galkina, O L; Önneby, K; Huang, P; Ivanov, V K; Agafonov, A V; Seisenbaeva, G A; Kessler, V G (Journal of materials chemistry. B, Materials for biology and medicine, 2015)
Nanocomposite dermal drug delivery systems based on cellulose nanofibers with grafted titania nanoparticles loaded by two antibiotic medicines from different classes, i.e. tetracycline (TC) and phosphomycin (Phos), were successfully produced by a "green chemistry" approach in aqueous media. The influence of a different surface binding mechanism between the drug molecule and modified cellulose nanofibers on the release of the drug and, as a result, on antimicrobial properties against common pathogens Gram-positive, Staphylococcus aureus and Gram-negative Escherichia coli was investigated. The disk diffusion method and broth culture tests using varying concentrations of drugs loaded to nanocomposites were carried out to investigate the antibacterial effects. The influence of UV irradiation on the stability of the obtained nanocomposites and their antibacterial properties after irradiation were also investigated, showing enhanced stability especially for the TC loaded materials. These findings suggest that the obtained nanocomposites are promising materials for the development of potentially useful antimicrobial patches.